2019
DOI: 10.1002/mbo3.923
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal development of the gut microbiota in healthy and diarrheic piglets induced by age‐related dietary changes

Abstract: Diarrhea is one of the most common enteric diseases in young piglets. Diverse factors such as an unstable gut microenvironment, immature intestinal immune system, early supplementary feeding, and weaning often induce dysfunction of gut microbiota, thus leading to a continuing high incidence of diarrhea in piglets. However, few studies have characterized the gut microbiota of diarrheic piglets following changes in diet and during the development of intestinal physiology. In this study, we used 16S rRNA gene seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 57 publications
8
42
1
1
Order By: Relevance
“…It is important to underline that the reduction, although significant, does not correspond to a dramatic drop in the content of both lactobacilli and bifidobacteria. Overall, for the Lactobacillus genus it seems that tributyrin has highlighted its gradual reduction that normally occurs in the weaning period [77] and for this reason, we take into consideration this modification as a signal that supplementation implies a gut microbiota modification.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to underline that the reduction, although significant, does not correspond to a dramatic drop in the content of both lactobacilli and bifidobacteria. Overall, for the Lactobacillus genus it seems that tributyrin has highlighted its gradual reduction that normally occurs in the weaning period [77] and for this reason, we take into consideration this modification as a signal that supplementation implies a gut microbiota modification.…”
Section: Discussionmentioning
confidence: 99%
“…The immune system of newborn animals is generally considered to be immature, which is closely related to a series of early diseases [1][2][3][4]. For instance, the immaturity of the intestinal immune system is regarded as one of the most important reasons for early-life diarrhea and early-weaning stress in mammals [5], and it has been confirmed that the development and maturation of the mammal intestinal immune system occur in infancy, even in the fetal period [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It is di cult to compare the core genera across studies. Besides age, commonly studies are done in pigs around weaning [41,42], housing and diet may also impact core genera. Moreover, it has been recently determined that when de ning the core microbiome in pigs, differences in study protocols have a signi cant impact and standardization of experimental techniques appear to be important [43].…”
Section: Discussionmentioning
confidence: 99%